DESIGN AND FABRICATION OF INTEGRATED INDUCTORS WITH POLYMER-FERROMAGNETIC CORE - Abdullahi, B. H.; Kebe, M.; Sagkol, H. (FUDMA Journal of Sciences, 2023)
The wireless communication system is rapidly improving with the integration of several Integrated Circuits (Ics) on a single chip, and the integration of elements such as resistors, transistors and capacitors was overcome without many difficulties, but the integration of high quality inductors at microwave frequencies still remains a big threat in scaling down remote communication devices. This is because high inductance inductors require large spacing and usually have smaller operating frequency range. Many Techniques has been used to augment the quality factor (Q-Factor) of the inductor, but implemented inductors using these techniques cannot operate over 5 GHz. Therefore, in this research we are aiming to show the improvement of performance after using a mixture of a polymer (SU8) and Ferromagnetic materials in the trenches of a spiral inductor by design of two types of inductors: one type uses SU8 and the other type uses FM-SU8 core and then compare the results of the these inductors, the fabrication method used is microfabrication processes which includes photolithography of photoresist and SU8, sputtering, lift-off and electroless-plating.